Edukasi Penanganan Hipertensi dengan Acupressure di Banjar Dinas Megati Kaja, Provinsi Bali: Education on Managing Hypertension with Acupressure in Banjar Dinas Megati Kaja, Bali Province - I Dewa Ayu Agra Darmawati; Kadek Buja Harditya; Komang Rosa Tri Anggaraeni (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Since the Covid-19 pandemic, several programs that were routinely carried out had to be stopped, one of which was the free medical treatment which was routinely carried out by the Selemadeg Timur I Public Health Center, Tabanan Regency, Bali. The cessation of free treatment at the Banjars in Selemadeg Timur sub-district, Tabanan Regency - Bali due to the Covid-19 pandemic has made people not carry out routine screening of their illnesses, especially hypertension. with hypertension. The aim is to provide knowledge to sufferers and families about handling hypertension at home. The activity was carried out through the provision of education in the form of providing leaflets about the management of hypertension with acupressure techniques and providing masks to prevent transmission of the corona virus-19 to 70 patriarchs located at Banjar Dinas Megati Kaja, Tabanan, Bali, Indonesia. The method used is through lectures, discussions, and demonstrations. The activity was carried out from 10 September - 12 September 2021. The entire Banjar Dinas Megati Kaja community accepted the assistance provided and the activity implementation ran smoothly. We wish that this activity can continue and become one of the programs of the Village